The changing ethos of human rights - Mahmoudi, Hoda; Brysk, Alison, 1960-; Seaman, Kate (Northampton, MA, USA : Northampton, MA, USA : Edward Elgar Publishing, 2021)
Utilizing the ethos of human rights, this insightful book captures the development of the moral imagination of these rights through history, culture, politics, and society. Moving beyond the focus on legal protections, it draws attention to the foundation and understanding of rights from theoretical, philosophical, political, psychological, and spiritual perspectives. The book surveys the changing ethos of human rights in the modern world and traces its recent histories and process of change, delineating the ethical, moral, and intellectual shifts in the field. Chapters incorporate and contribute to the debates around the ethics of care, considering some of the more challenging philosophical and practical questions. It highlights how human rights thinkers have sought to translate the ideals that are embodied in the Universal Declaration of Human Rights into action and practice. Interdisciplinary in nature, this book will be critical reading for scholars and students of human rights, international relations, and philosophy. Its focus on potential answers, approaches, and practices to further the cause of human rights will also be useful for activists, NGOs, and policy makers in these fields.
Introduction to The changing ethos of human rights / Matthew S. Weinert. Cultural heritage, cultural rights and care ethics / Michael L. Penn -- Dignity and treating others merely as means / Samuel Kerstein -- Making rights work : constructing care in a post-liberal world / Alison Brysk -- Race and feminist care ethics : intersectionality as method / Parvati Raghuram -- Difficult care : examining women's efforts in the Islamic Republic of Iran / Hoda Mahmoudi -- Empathy, caring, and the defense of human rights in a digital world / Kate Seaman -- Cultural heritage, cultural rights and care ethics / Matthew S. Weinert.
Includes bibliographical references and index.
Keywords: Human rights; Human rights